Model Pengembangan Usaha Menengah Kecil dan Mikro (UMKM) Herbal Berbasis Digital: Studi Kasus Pada Jamu Kito Kota Bengkulu - Dina Hasta Ningsih; Diogi Putra Befa; Sarina (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
Digital transformation has become a critical factor in enhancing the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs), particularly those operating in the herbal-based industry. However, limited studies have comprehensively examined the integration of product innovation, digital marketing, customer relationship management (CRM), and organizational resilience within herbal MSMEs in regional areas of Indonesia. This study aimed to analyze the development strategy of Jamu Kito, a herbal MSME in Bengkulu City, and to formulate a model for strengthening its competitiveness in the digital era. The research was conducted in April 2025 using a qualitative case study approach. Data were collected through in-depth interviews with the business owner, field observations, and business documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicated that Jamu Kito’s competitive advantage was derived from the utilization of natural ingredients without synthetic preservatives, customer-driven product innovation, digital-based marketing activities, and customer relationship management practices that strengthened customer trust and loyalty. The study also revealed that the business demonstrated strong organizational resilience through adaptive strategies implemented after a major fire incident. The novelty of this research lies in the development of an integrated competitiveness model that combines entrepreneurial orientation, herbal product innovation, digital marketing, customer relationship management, and organizational resilience. The proposed model provides both theoretical and practical contributions to the development of sustainable herbal MSMEs in Indonesia.